Short-Term Effects of Lupin vs. Whey Supplementation on Glucose and Insulin Responses to a Standardized Meal in a Randomized Cross-Over Trial - Schopen, Kathrin; Ewald, Ann C.; Johannes, Bernd W.; Bloch, Wilhelm; Rittweger, Jörn; Frings-Meuthen, Petra (Frontiers in Physiology, 2017)
Background Whey protein is known to reduce postprandial glycaemia in people with type 2 diabetes mellitus. Lupin as a vegetable source of protein could be considered as an alternative, as the percentage of vegetarian and vegan consumers is raising. The present study compares the acute glycemic effects of whey and lupin in healthy volunteers following a carbohydrate-rich reference meal. Methods In cross-over design, three standardized meals (reference meal; reference meal + whey; reference meal + lupin) were provided to 12 healthy male and female volunteers, aged between 23 and 33, in a balanced, randomized order. Volunteers’ blood glucose and insulin concentrations were analyzed at baseline and at seven time points following the ingestion of the meals. Results The supplementation of whey or lupin significantly blunted the postprandial increase in blood glucose concentrations compared to the reference meal (p˂0.001). In the overall statistical analysis, this effect was comparable for whey and lupin [Δ AUC whey-lupin=8%, 0-60 minutes area under the curve (0-60 min AUC), p=0.937], with a blunting effect of -46% by whey (p=0.005, 0-60 min AUC) and of -54% by lupin (p<0.001, 0-60 min AUC). When comparing whey and lupin data only, the insulin increase was found to be more pronounced for whey protein than for lupin supplementation (Δ AUC whey-lupin=39%, 0-60 min AUC, p=0.022). However, when comparing the insulin response of each supplementation to the one of the reference meal, no differences could be detected (whey p=0.259, 0-60 min AUC; lupin p=0.275, 0-60min AUC). Conclusions Results suggest that lupin and whey can both lower the increase of postprandial blood glucose concentrations to a comparable extent, implying the usability of lupin to reduce postprandial glycaemia. However, the insulin response following the supplementations to a carbohydrate-rich meal seems to differ for these two protein sources. Clinical trial registry number and website: The trial was retrospectively registered on ClinicalTrials.gov under number NCT02413671.